Usability Evaluation Of The Academic Information System Using The Concurrent Think-Aloud, Webuse, And Sus Methods - Sarasmayana, Ketut Yoga; Dewi , Luh Joni Erawati; Sunarya, I Made Gede (Journal of Computer Networks, Architecture and High Performance Computing, 2024)
This research was motivated by the situation that the academic information system (SIAKAD) Universitas Teknologi Indonesia (UTI) had never been tested for usability based on user responses. Apart from that, the flow that occurs in the UTI academic information system is not yet coherent. From the user's side, the information guide feature for using SIAKAD UTI is not yet available. Based on this, the research aimed to: 1) describe the results of Usability evaluation using the Concurrent Think-Aloud and Webuse methods on the Academic Information System of Indonesia Technology University; 2) describe recommendations for usability evaluation of the Concurrent Think-Aloud and Webuse methods on the Academic Information System of the Indonesia Technology University; and 3) create a simulation of SIAKAD UTI development and describe the test results using the System Usability Scale (SUS) method. The research method used a mix of qualitative and quantitative methods, so that data obtained is more comprehensive, valid, reliable, and objective. Usability evaluation data through the Concurrent Think-Aloud method was collected using interviews, usability evaluation through the Webuse method was collected using a questionnaire, and satisfaction data through the SUS method was collected using a questionnaire. The results of the development carried out in this research can be concluded as follows. (1) The SIAKAD UTI evaluation results through the Concurrent Think-Aloud method showed that many navigation buttons did not function, inconsistent button features, disproportionate location/buttons position, and inappropriate color selection. Therefore, the evaluation results through the Concurrent Think-Aloud Method showed that SIAKAD UTI needs to be improved. (2) The SIAKAD UTI evaluation results through the Webuse method obtained an overall mean value of usability points, namely 0.23, in the range 0.2 < x ?0.4 with a usability level category of Poor, which means that it is necessary to improve the development of SIAKAD UTI. (3) Based on the evaluation results, a SIAKAD UTI development simulation was carried out, followed by a satisfaction test using SUS. The average score obtained after processing the assessment scores from respondents with an average value of 97.35, which showed that respondents were very satisfied using the results of the SIAKAD UTI development simulation.